Adipogenesis induces growth inhibition of dedifferentiated liposarcoma. Issue 8 (28th June 2019) - Kim, Yu Jin; Yu, Dan Bi; Kim, Mingi; Choi, Yoon‐La
Abstract: Well‐differentiated liposarcoma (WDLPS) and dedifferentiated liposarcoma (DDLPS) are the most common types of liposarcoma. Although WDLPS and DDLPS patients receive intensive treatment including radical surgery and systemic therapy, their overall 5‐year survival rates are 90% and 30%, respectively, indicating that DDLPS is clinically more aggressive. We examined whether adipogenic stimulation induces adipogenesis in human WDLPS/DDLPS cells by using dexamethasone, indomethacin, insulin, and 3‐isobutyl‐1‐methylxanthine (IBMX), all putative medications or drugs. Functional in vitro experiments showed that treatment with these four compounds induced adipogenic potency by transcriptional and translational upregulation of genes related to the maintenance of stemness and adipogenic differentiation. Using in vivo xenograft models, we found that the induction of stemness and adipogenesis inhibited the tumorigenic potency of DDLPS. This study suggests a potential application of drug repositioning in which adipogenesis‐inducing compounds could be used to treat DDLPS patients in a clinical setting. Abstract : Induction of adipogenesis using four compounds used as medication or possible drug inhibited the tumor potency of DDLPS. Our finding suggests the potential application of drug repositioning in which adipogenic‐inducing compounds can be used to treat DDLPS patients in clinical therapy.